Development of an Accrual-Based Accounting Information System Using a Performance Measurement System - Anak Agung Surya Pradhana; I Wayan Kintara Anggara Putra (INFOTEKS (Information Technology, Computer and Sciences), 2026)
The integration of accounting and performance measurement systems is a crucial advancement for small and medium-sized enterprises (SMEs), which often face challenges in managing financial processes efficiently. Traditional accounting systems, while reliable, lack real-time financial insights and performance metrics necessary for informed decision-making. This study addresses the problem by proposing an accrual-based Accounting Information System (AIS) integrated with a Performance Measurement System (PMS). The motivation behind this work is to enhance financial decision-making in SMEs by automating key accounting functions and providing real-time performance feedback. The proposed system automates revenue recognition, expense matching, and cost allocation, while simultaneously tracking key performance indicators (KPIs) such as profitability and return on assets. The system was evaluated in a case study involving several SMEs, where it demonstrated improved accuracy in financial reporting, reduced manual errors by 30%, and enhanced decision-making by providing real-time performance insights. Usability testing revealed high satisfaction from users, although additional training was recommended to fully leverage the system’s capabilities. The system's scalability for larger organizations remains an area for future exploration. Future work will focus on refining predictive analytics to further improve financial forecasting and expanding the system’s scalability to accommodate larger enterprises. The results highlight the potential of integrating accrual accounting with performance measurement to enhance financial management in SMEs, offering a practical solution for improved financial decision-making.